1994
DOI: 10.1021/jm00044a014
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structure-Activity Relationships of Novel Retinoid X Receptor-Selective Retinoids

Abstract: Two series of potent retinoid X receptor (RXR)-selective compounds were designed and synthesized based upon recent observation that (E)-4-[2-(5,5,8,8-tetramethyl-5,6,7,8-tetrahydro-2-naphthalenyl)-1- propenyl]benzoic acid (TTNBP) binds and transactivates only the retinoic acid receptor (RAR) subtypes whereas (E)-4-[2-(3,5,5,8,8-pentamethyl-5,6,7,8- tetrahydro-2-naphthalenyl)-1-propenyl]benzoic acid (3-methyl TTNPB) binds and transactivates both the RAR and RXR subfamilies. Addition of functional groups such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
297
0
4

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 355 publications
(303 citation statements)
references
References 7 publications
2
297
0
4
Order By: Relevance
“…54 Increased binding affinity from retinoids exhibiting increased rigidity has been reported for a number of other synthetic retinoids in both the RARs and RXRs. 55,56 EC19 exhibited atypical retinoid binding according to simulation due to its meta-carboxylate substituent. This resulted in the sacrifice of a key hydrogen bond to the polar cluster at the bottom of the pocket, and also served to give non-ideal hydrophobic interactions around the hydrophobic region in RARÎą and RARÎł.…”
Section: Discussionmentioning
confidence: 99%
“…54 Increased binding affinity from retinoids exhibiting increased rigidity has been reported for a number of other synthetic retinoids in both the RARs and RXRs. 55,56 EC19 exhibited atypical retinoid binding according to simulation due to its meta-carboxylate substituent. This resulted in the sacrifice of a key hydrogen bond to the polar cluster at the bottom of the pocket, and also served to give non-ideal hydrophobic interactions around the hydrophobic region in RARÎą and RARÎł.…”
Section: Discussionmentioning
confidence: 99%
“…Bexarotene is highly selective for the RXRs, and was the first 'rexinoid' to undergo clinical development. [63][64][65] The drug has received EMEA approval in Europe for the treatment of skin manifestations in advanced CTCL. 66 Although the precise mechanisms are unknown, in vitro studies have shown that bexarotene can inhibit growth in tumour cell lines and cause in vivo tumour regression in animal models: the drug also stimulates apoptosis.…”
Section: Rexinoidsmentioning
confidence: 99%
“…2 Defective retinoid signaling and deficiency of apolipoprotein E (ApoE) are closely associated with Alzheimer's disease (AD). 3 Bexarotene (4-[1- (3,5,5,8,8-pentamethyltetralin-2-yl)-ethenyl]benzoic acid, Figure 1), an FDA-approved selective RXR agonist, 4 has recently been demonstrated to induce clearance of β-amyloid from the brains of murine AD models through activation of the APOE gene, which is the most indicative genetic risk factor for late-onset AD. 5 In vitro and in vivo studies also suggest that bexarotene is acting on RXRs, and not directly on β-amyloid or by compromising the blood−brain barrier.…”
mentioning
confidence: 99%